Problems in the establishment of civil reparation in crimes of femicide - Salcedo Guevara, Margarita (2020)
The Civil Reparation it has a satisfactory compensatory support for the crime victim. However, in the judicial practice, in the crime against the Life, the Body and the Health in the modality of Femicide, despite its seriousness, it is verified that there is not uniformity of judicial criteria in concepts that it comprises, there is generally inaction from the Civil Actor and the Public Ministry in the damage accreditation, reason why the decisions of the judges do not satisfy a just and dignified civil reparation.